Infant Baptism in the First-Century Presupposition Pool - Steven A. Nicoletti (Tyndale Bulletin, 2015)
The debate over infant baptism in the apostolic church was classically captured in the exchanges between Joachim Jeremias and Kurt Aland. Most debates have focussed on ‘reading between the lines’ of first-century Christian texts, and have yielded little resolution of the New Testament’s silence. Such studies often fail to address the significance of the silence itself, within its original context. In this paper I examine the practices of first-century Judaism and Graeco-Roman religions regarding infant initiation and participation in their parents’ religion, including the Graeco-Roman practice of the dies lustricus and the involvement of children in Graeco-Roman worship. Using Theo Vennemann’s concept of presupposition pools, I will ask how the early church’s silence should be interpreted in light of the original audiences’ presuppositions. I will argue that since the New Testament and other surviving works of the early church do not address their audiences’ presupposition that their infants would be initiated into their religion, it indicates that they shared rather than challenged this widely held assumption. The New Testament’s silence is therefore best interpreted as indicating the practice of infant baptism.